MEDIA APPLICATION OF FLASH BASED ANIMATION ON EVALUATION COURSE - Sugiharti, Gulmah (International Journal of Research -GRANTHAALAYAH, 2019)
This research is an application of animation media that has been developed previously. The purpose of this study is to look at the effect of flash-based animation media that has been developed on improving learning outcomes in Chemistry Learning Outcomes Evaluation courses, and see the percent increase in student learning outcomes As a sample, the 2016 students consisted of 2 classes as an experimental class and a control class in the chemistry department at Unimed. After a normality test and a homogeneity test, the hypothesis is tested using a t test, and an increase in learning outcomes using a normalized gain test. From the results of the study obtained average pre-test learning outcomes in the experimental group and in the control group of 31.6 and 33.5. While the average post-test learning outcomes in the experimental group (79.5) and in the control group (75.0). From the average value, it can be seen that students who are taught by using the animation media developed by FLAS, have a higher average value compared to students who are taught without using media. While the gain of an increase in student learning outcomes in the experimental class by 70.6% and an increase in the increase in student learning outcomes in the control class by 63.4%. So it was concluded that flash-based animation media is good to be used in learning the Chemistry Learning Outcomes Evaluation course.